Analysis of the Application of Business Ethics (Case Study of UD. Umega Roti Kacang Hj. Eliya Lubis, City of Tebing Tinggi) - Ridha Lasthree Putri; Hasyim; Mariska Anggraini Achmad; Sri Jingkatna (Formosa Journal of Applied Sciences, 2023)
This study aims to determine whether business ethics has been applied to UD.Umega Roti Kacang Hj.Eliya Lubis, Tebing Tinggi City and to determine the impact of the application of business ethics on business progress at UD. Umega Roti Kacang Hj.Eliya Lubis, Tebing Tinggi City. This type of research is a qualitative research with a descriptive approach. The informants in this study are the owner, employees and customers, each of whom is 1 person. The results of this study indicate that business ethics at UD.Umega Roti Kacang Hj.Eliya Lubis Tebing Tinggi City has been well implemented, this is seen from the results of interviews that have been conducted with business owners, employees and customers. The application of business ethics itself can also be seen directly by the high interest of customers, which automatically means that the business being run will grow and operate smoothly.